(untitled) (Research, Society and Development, 2020)
The present study aimed to identify enteroparasites in food handlers described in the literature. This is an integrative literature review, which obtained a total of eleven articles, in which a thorough analysis of the studies available in full in the databases: International Literature on Health and Biomedical Sciences (Pubmed), Academic OneFile and Scientific Electronic Library Online (SciELO). We identified 100 articles, of which after an analysis of the studies, 11 articles addressed the proposed theme and met the inclusion criteria. From the comprehension and analysis of the data obtained by reading the selected studies, it was found that 100% of the works referred to field research. The food handler should maintain good hygiene habits to ensure the production of quality food, and have knowledge to prevent parasite involvement.